Expressive and Receptive Language Disorder of Shaun Murphy in The Good Doctor Series - Rizqi Fatkhur Rokhim; Rohmani Nur Indah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
The autistic savant is a rare condition that occurs in people with autism that affects the ability in expressing and receiving language information appropriately. This study aimed to describe the expressive and receptive language disorder of Shaun Murphy as the autistic savant main character in The Good Doctor movie. It used descriptive qualitative method to get a deep understanding of the language disorder as portrayed in the movie. The data were taken from Shaun Murphy’s utterances transcribed from The Good Doctor movie. The analysis employed the theory of Carroll to describe how autistic savant person communicates with others. The findings from this study indicated that of the twelve utterances produced by Shaun Murphy, only four from six types of language disorders were found. They included stuttering, phonological disorder, difficulty in understanding the concept, and difficulty in following directions. Shaun Murphy dominantly produced stuttering. He often spoke with stammering, hanging, and repetition of sentences. In this case, the language disorders of the main character appeared when he was panic, happy, anxious, and unconfident; which could influence his way of communication.